Persistence of emotion in the process of inoculation: experiencing post-attack threat, fear, anger, happiness, sadness, and surprise. Issue 5 (19th October 2020) - Ivanov, Bobi; Hester, Erin B.; Martin, Joe C.; Silberman, Will; Slone, Amanda R.; Goatley-Soan, Sean; Geegan, Sarah; Parker, Kimberly A.; Herrington, Taban F.; Riker, Seth; Anderson, August
ABSTRACT: This investigation assessed the mechanisms that contribute to post-attack attitudinal persistence. A three-phase experiment was designed to uncover why inoculation works even after it has been challenged by a counterattitudinal attack. The results of this study show that threat, both motivational and apprehensive, not only persists after the attack, but it may be heightened by an increase in post-attack fear and sadness . Greater anger and less happiness were also expressed by inoculated individuals in response to the attack. An increase, rather than decrease, in surprise was a surprising outcome. Taken together, the findings from this study suggest that the effects of inoculation continue to persist beyond the attack as threat and multiple other emotions interact to form and inspire a formidable attitudinal barrier that endures over time.